THE BIOCHEMICAL ALTERATION AND DNA DAMAGE IN RATS (RATTUS RATTUS) AFTER CHRONIC INTRAPERITONEALLY INJECTION TO PURIFIED MICROCYSTIN-LR FROM ANABAENA CIRCINALIS - Khadairi, Maher M; Al-amari, Moayed Jy; Al-mamoori, Ayad Mj (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study determined the effect of purified microcystin-leucine arginine (MC-LR) on biochemical and DNA damage parameters in rats. Methods: Utilization of preparative high-performance liquid chromatography in analysis, purification and collection of MC-LR, then intraperitoneally injection of purified MC-LR to rats. At the end of exposure, animals were sacrificed, and liver cell was isolated to measure the biochemical markers such as superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) as well as measured malondialdehyde (MDA), reactive oxygen species (ROS) and cytochrome P450 (Cyt P450), and DNA damage markers such as comet length, tail length, and tail moment were measured with the single cell gel electrophoresis also called comet assay. Results: The present results showed significantly increased activities of SOD as well as concentration of MDA, ROS with increasing concentration of MC-LR but the activities of CAT and GSH, as well as Cyt P450, were significantly decreased with increasing MC-LR dose while makers of DNA damage such as comet length, tail length, and tail moment also significantly increased with increasing MC-LR dose. Conclusion: This study demonstrated that chronic exposure to MC-LR toxin can induce alteration of biochemical and DNA damage markers.